Rare and Endangered Land Mollusks in California - Barry Roth (Hello World!, 1972)
The varied snail and slug fauna of California includes species and subspecies whose existence is presently endangered or potentially threatened by habitat destruction. Some of these are vulnerable because of rarity or narrowly restricted ranges; other, wide- ranging, species have been depleted over portions of their ranges. A compilation is supplied of 127 California snails and slugs considered rare and/or endangered, with their geographic ranges, habitat notes, and observed or reported threats to various species and subspecies. Major genera represented are Helminthoglypta, with 42 taxa, Micrarionta, with 26, and Monadenia, with 20.